CONVERSATIONAL IMPLICATURE IN DAILY COMICS OF KOMPAS NEWSPAPER JANUARY-FEBRUARY 2022 EDITION: IMPLIKATUR PERCAKAPAN DALAM KOMIK HARIAN KORAN KOMPAS EDISI JANUARI-FEBRUARI 2022 - Ricky Imam Saputro; Bram Denafri S (Jurnal Kata, 2023)
Implicature in Kompas daily newspaper comics is used to convey criticism of social issues or problems of society implicitly. The purpose of this study is to describe the form of implicature in conversations contained in the January-February 2022 edition of Kompas daily comics using George Yule's theory. The method used in this research is descriptive qualitative and use listening techniques, note-taking techniques, and photo techniques. The results in this study found conversations in comics that contain conventional implicature and non-conventional implicature those data that contains themes that raise about social conditions, social criticism of government, criticism of leaders in society. The conclusion of this research are obtained various meanings that have their own values from each utterance in comics published in the January-February 2022 edition of Kompas newspaper.